Security Requirements for Multimedia Archives. (3rd August 2015) - Park, Sang Bae
Abstract : With the explosive growth of various multimedia contents, digital archives are used to store those contents accordingly. In contrast to the traditional storage systems in which data lifetime is measured in months or years, data lifetime in the archive is measured in decades. This longevity of contents causes new security issues that threat the archive systems. In this paper, we discuss these new security issues in perspective. And we suggest some security requirements for digital archives.